Process-Based Software Project Management (CRC Press, 2009)
Not connecting software project management (SPM) to actual, real-world development processes can lead to a complete divorcing of SPM to software engineering that can undermine any successful software project. By explaining how a layered process architectural model improves operational efficiency, Process-Based Software Project Management outlines a new method that is more effective than the traditional method when dealing with SPM.